Synthesis And Characterization Of Alginate-Cellulose Xanthate Beads From Corn Stalk With NaCL As Porogen - Wahyu Adhi Putra Rohmatullah; Eny Yulianti; Lilik Miftahul Khoiroh; Rif'atul Mahmudah (Research Center for Biotechnology - Indonesian Institute of Sciences (LIPI), 2020)
In this study, the synthesis of porous beads from corn stalks was carried out. The cellulose extracted from corn stalks was converted into cellulose xanthate and combined with alginate to form porous alginate-cellulose xanthate beads by the ionic gelation method. This study attempted to use sodium chloride (NaCl) as a porogen and zinc acetate as a crosslinker. Beads were characterized to determine the porosity, swelling properties, and functional groups using Fourier Transform Infra-Red (FTIR). The geometry of beads was analyzed by optical microscopy, and its surface morphology was analyzed by Scanning Electron Microscopy-Energy Dispersive X-ray (SEM-EDX). The results showed that corn stalks as agricultural waste material could be used to synthesize porous beads material. The swelling and porosity of beads increased with increasing concentration of NaCl. The presence of porogen has increased beads formation. The results demonstrate the crosslinks between zinc acetate and alginate were successfully characterized using FTIR. NaCl concentration of 9.5% resulted in the highest swelling properties (52.80%) and porosity (81.4%) of the beads.